Adsorption of Basic Red 2 onto Peanut Shell: Batch and Column Studies - Sakalar, Neslihan; Hilal Bilir, M.; Acemioglu, Bilal; Hakki Alma, M. (Asian Journal of Chemistry, 2010)
In this study, peanut shell was utilized as an adsorbent for the adsorption of basic red 2 from aqueous solution. Adsorption experiments were performed as a function of contact time, initial dye concentration, temperature and pH. While the amount of the dye adsorbed onto peanut shell was increasing with increasing contact time, initial dye concentration, it decreased with increasing solution temperature. The most adsorption was observed at pH 5. The maximum adsorptions were between 84.70 and 98.86 % under all the experimental conditions studied such as concentration, pH and temperature. Equilibrium data was consistent with Freundlich isotherm. Adsorption kinetic was in the best agreement with the pseudo-second order model. Furthermore, SEM and FT-IR studies of peanut shell were performed and the results obtained were interpreted. Column adsorption studies were also done. The percentages of basic red 2 adsorbed in column were more than 99 %.